2021
DOI: 10.1364/oe.433017
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-insensitive achromatic metalens based on computational wavefront coding

Abstract: Broadband achromatic metalens imaging is of great interest in various applications, such as integrated imaging and augmented/virtual reality display. Current methods of achromatic metalenses mainly rely on the compensation of a linear phase dispersion implemented with complex nanostructures. Here, we propose and experimentally demonstrate a polarization-insensitive achromatic metalens (PIA-ML) based on computational wavefront coding. In this method, simple circular or square nanopillars are individually coded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…However, metalenses still severely suffer from poor imaging quality under broadband illumination due to serious chromatic aberration [10][11][12][13] . Several pioneering works have demonstrated achromatic metalens operating over a broad wavelength range [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . However, according to the fundamental limitations of the achromatic flat lens, the diameter of an ideal achromatic metalens (under the diffraction limit) is restricted by its thickness (the max height each nano-unit can achieve) [18][19][20][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…However, metalenses still severely suffer from poor imaging quality under broadband illumination due to serious chromatic aberration [10][11][12][13] . Several pioneering works have demonstrated achromatic metalens operating over a broad wavelength range [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . However, according to the fundamental limitations of the achromatic flat lens, the diameter of an ideal achromatic metalens (under the diffraction limit) is restricted by its thickness (the max height each nano-unit can achieve) [18][19][20][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the function of those elements is usually limited to the polarization filtering. Recently, optical metasurfaces with various manipulation characteristics of the light wave have been proposed and demonstrated, such as achromatic imaging metalens, optical hologram, , and polarization control and conversion. Moreover, the multifocal polarization-dependent metalenses have also attracted lots of attention due to the superior characteristics of multiple functions, lightweight, and integration, from which the incident light with different linear or circular polarization states is focused/imaged at different positions. In 2016, Khorasaninejad et al demonstrated a multispectral chiral imaging metalens in the visible wavelength band, in which two sets of TiO 2 nanopillar arrays corresponding to right-handed circular polarization (RCP) and left-handed circular polarization (LCP) states, respectively, were arranged as the Pancharatnam–Berry phase (P–B phase) . The lights with different CP states and wavelengths are, therefore, imaged at the different positions by the two sets of metalens.…”
Section: Introductionmentioning
confidence: 99%
“…Several pioneering works have demonstrated achromatic metalens operating over a broad wavelength range [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] . However, according to the fundamental limitations of the achromatic flat lens, the diameter of an ideal achromatic metalens (under the diffraction limit) is restricted by its thickness (the max height each nano-unit can achieve) [18][19][20][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%